Nyai Hannah and the Qur’anic Preaching in Indonesian Social Media - Mukaromah, Kholila; Silviana, Ika; Maula, Nabila An'imatul; Dewi, Subkhani Kusuma (QOF, 2024)
This study aims to reveal Nyai Hannah’s motives in preaching the love of the Qur’an and its influence on preserving Qur’anic values in the digital sphere. Nyai Hannah is one of the female scholars and hafiẓah (female memorizer of the Qur’an) figures from the Pesantren Lirboyo who is widely known, including through social media. The study includes living Qur’an research with a qualitative-descriptive approach and uses the life history method. Data collection is done by purposive sampling through all parties encountering Nyai Hannah: santris (pesantren students), virtual students (viewers/followers) on social media, and Nyai Hannah herself. The Nyai’s role in internalizing Qur’anic messages through videos of reciting the Qur’an, inspirational quotes, and cheerful invitations spread across social media platforms such as Whatsapp, YouTube, Instagram, and even TikTok.  In her contents, she utilizes various resources -symbolic, social, and material- to optimize her preach. There is a shift in preaching motives from private to public throughout her activities. The combination of personal capacity, leadership, social relations, and technological adaptation signifies her role in preserving the values of the Qur’an in the digital era, where she accentuates inclusive and relevant approach to younger generation. Her presence emphasizes the importance of women’s role in spreading Islamic messages and shows that domestic and public activities may intertwin each other. This study is expected to accomodate studies on the performative function and living Qur’an based on digital media to be more responsive to socio-cultural dynamics and technological developments.